2001
DOI: 10.1051/0004-6361:20010064
|View full text |Cite
|
Sign up to set email alerts
|

The structure of radiative shock waves

Abstract: Abstract. The grid of the models of radiative shock waves propagating through partially ionized hydrogen gas with temperature 3000 K ≤ T1 ≤ 8000 K and density 10 −12 gm cm −3 ≤ ρ1 ≤ 10 −9 gm cm −3 is computed for shock velocities 20 km s −1 ≤ U1 ≤ 90 km s −1 . The fraction of the total energy of the shock wave irreversibly lost due to radiation flux ranges from 0.3 to 0.8 for 20 km s −1 ≤ U1 ≤ 70 km s −1 . The postshock gas is compressed mostly due to radiative cooling in the hydrogen recombination zone and fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…The authors fulfilled calculations of a one-dimensional radiative shock wave and demonstrated the formation of a region with a small gradient of the plasma parameters: temperature, pressure, and density (see Figures 3 and 4 in Katsova et al (1981)). This result is confirmed by the calculations of the radiative cooling behind a shock front in the atmospheres of cool stars (see Fadeyev & Gillet (2001) and Belova et al (2014)) with a more detailed account for the elementary processes in the plasma: ionization, recombination, bremsstrahlung, excitation and de-excitation of discrete levels of atoms and ions as well as radiation scattering at the frequencies of spectral lines.…”
Section: Introductionsupporting
confidence: 57%
“…The authors fulfilled calculations of a one-dimensional radiative shock wave and demonstrated the formation of a region with a small gradient of the plasma parameters: temperature, pressure, and density (see Figures 3 and 4 in Katsova et al (1981)). This result is confirmed by the calculations of the radiative cooling behind a shock front in the atmospheres of cool stars (see Fadeyev & Gillet (2001) and Belova et al (2014)) with a more detailed account for the elementary processes in the plasma: ionization, recombination, bremsstrahlung, excitation and de-excitation of discrete levels of atoms and ions as well as radiation scattering at the frequencies of spectral lines.…”
Section: Introductionsupporting
confidence: 57%
“…They are followed by recombinations and de-excitations that produce the observed emission lines. In this radiative region of the shock wake, the gas density is typically 50 to 100 times that of the unperturbed gas in front of the shock (Fadeyev & Gillet 2001). If the shock Mach number is high enough, the temperature and the density in the de-excitation region of the wake could be sufficient to produce He I and He II emission lines.…”
Section: Helium Emissions In Rr Lyrae Starsmentioning
confidence: 99%
“…One of the most important aspects characterizing the radiative shocks is that the largest part of their energy is lost as radiation. Indeed, comparing the preshock and post-shock outer boundaries, Fadeyev & Gillet (2001) have shown that in a pure hydrogen gas, most of the kinetic energy of the gas flow is irreversibly lost. When the shock velocity becomes higher than 60 km s −1 , radiative losses increase very rapidly with increasing upstream velocity.…”
Section: The Second Required Process: the Decrease Of The Average Effmentioning
confidence: 99%